Executive control over unconscious cognition: attentional sensitization of unconscious information processing - Kiefer, Markus (Frontiers in Human Neuroscience, 2012)
Unconscious priming is a prototypical example of an automatic process, which is initiated without deliberate intention. Classical theories of automaticity assume that such unconscious automatic processes occur in a purely bottom-up driven fashion independent of attentional control mechanisms. In contrast to these classical theories, our attentional sensitization model of unconscious information processing proposes that unconscious processing is susceptible to attentional top-down control and is only elicited if the cognitive system is configured accordingly. It is assumed that unconscious processing depends on attentional amplification of task-congruent processing pathways. This article provides an overview of the latest research on executive control influences on unconscious information processing. I introduce refined theories of automaticity with a particular focus on the attentional sensitization model of unconscious cognition which is specifically developed to account for various attentional influences on different types of unconscious information processing. In support of the attentional sensitization model, empirical evidence is reviewed demonstrating attentional top-down influences on unconscious cognition in the domains of visuo-motor, semantic and emotional processing: Subliminal priming depends on attentional resources, is susceptible to stimulus expectations and is influenced by action intentions and task sets. This suggests that even unconscious processing is flexible and context-dependent as a function of higher-level executive control settings. It is discussed that the assumption of attentional sensitization of unconscious information processing can accommodate conflicting findings regarding the automaticity of processes in many areas. This theoretical view has the potential to stimulate future research on the cognitive control of unconscious processing in healthy and clinical populations.